The effect of arterial stiffness on the severity and progression of primary open angle claucoma in Malay patients - Kwong Yew, Kiu (2015)
Introduction The pathogenesis of glaucoma is still unclear. The direct effect of elevated intraocular pressure (IOP) has been proposed as important risk factor for developing of glaucomatous optic neuropathy (GON) based on mechanical theory. Despite well controlled IOP, glaucoma still progress in some patients. Vascular theory suggested that insufficient blood supply causes GON. A combination of high IOP and inadequate ocular perfusion may theoretically accelerate GON lead to rapid progression and more severe disease. Objectives Our objectives are to compare the mean of arterial stiffness between POAG patients and controls and to compare the mean of arterial stiffness on severity and progression of POAG. Methodology 110 Malay patients were recruited for this study. 55 patients were POAG while 55 were age and gender matched controls. Arterial stiffness was measured in pulse wave analysis ( PWA) and pulse wave velocity (PWV) parameters using sphygmocor device. Results Mean age was 66.9 ± 9.0 years in POAG group and 66.6 ± 8.9 years in controls. PWA was 26.98 ± 6.15% in POAG and 25.90 ± 5.39% in controls while PWV was 15.73 ± 4.14 m/s in POAG and 15.18 ± 3.26 m/s in controls. There were no significant differences of PWA and PWV between the two groups. Meanwhile, no significant difference of PWA and PWV on the severity and progression of POAG were noted. However, PWV showed significant difference on progression of POAG after analysed with multivariate ANCOVA with p < 0.05. Conclusion In this study, there were no significant difference of arterial stiffness between POAG and controls and the severity of POAG. PWV was found to be significant on progression of glaucoma after controlling the confounding factors.